2023
DOI: 10.3390/ijerph20053885
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Copper Ions from Wastewater: A Review

Abstract: Copper pollution of the world’s water resources is becoming increasingly serious and poses a serious threat to human health and aquatic ecosystems. With reported copper concentrations in wastewater ranging from approximately 2.5 mg/L to 10,000 mg/L, a summary of remediation techniques for different contamination scenarios is essential. Therefore, it is important to develop low-cost, feasible, and sustainable wastewater removal technologies. Various methods for the removal of heavy metals from wastewater have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 157 publications
0
22
0
Order By: Relevance
“…25 Although established technologies have been able to bring down high concentrations of Cu in effluents to sub ppm levels, they still do not meet certain standards of Cu in drinkable water. 26,27 Moreover, the utilization of membrane technologies in water treatment is costly due to the high power consumption. In this study, the addition of keratin amyloid fibrils into activated carbon to form a hybrid membrane further improved the removal efficiency (E) from 78 to 97%, reducing Cu concentrations from 2 ppm to 60 ppb (Figure 4a) and serving as high Cu-adsorbing fillers in the carbon matrix (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…25 Although established technologies have been able to bring down high concentrations of Cu in effluents to sub ppm levels, they still do not meet certain standards of Cu in drinkable water. 26,27 Moreover, the utilization of membrane technologies in water treatment is costly due to the high power consumption. In this study, the addition of keratin amyloid fibrils into activated carbon to form a hybrid membrane further improved the removal efficiency (E) from 78 to 97%, reducing Cu concentrations from 2 ppm to 60 ppb (Figure 4a) and serving as high Cu-adsorbing fillers in the carbon matrix (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In case the keratin polymer was not formed, a comparative adsorption study of keratins, DAA polymers, and KH/DAA towards Cu( ii ) was conducted following conditions in which a mixture of 50 mL solution containing 500 mg L −1 Cu( ii ), 30 mg adsorbent was used and kept at 30 °C for 12 h. It has been noted that the concentration of copper in wastewater differs significantly (2.5 mg L −1 to 10 g L −1 ) from different resources. 37 The concentration of copper in the study was 500 mg L −1 to make sure that the conclusion can be applied to different conditions. Our findings revealed that keratins exhibited moderate adsorption capacity towards Cu( ii ) (29.7 mg g −1 ), while the DAA polymer demonstrated a higher capacity for Cu( ii ) (215.6 mg g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Copper, a quintessential transition metal naturally abundant, is classified among heavy metals . Copper ions can infiltrate surface and groundwater systems, potentially contaminating drinking water sources and posing a threat to human health . Copper ion pollution has been escalating in the global aquatic environment and has been recognized as a principal heavy metal contaminant due to its associated health risks .…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical methods include membrane separation, ion exchange, chemical precipitation, electrochemistry, and adsorption, whereas the biological methods encompass biosorption, bioprecipitation, and biomineralization . While the aforementioned treatment technologies can be utilized for the removal of copper ions, they each have inherent advantages and limitations . The adsorption method offers several advantages, such as the ready availability of materials, straightforward operation, low cost, ready availability of materials, rapid reaction rate, and effective treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%